Purposeful empathy : tapping our hidden superpower for personal, organizational, and social change - Nowak, Anita (Tantor Media, Inc., 2023)
Empathy has never been more important, yet we're living in an era of a massive empathy deficit. At the same time, workplace culture has changed dramatically. Leaders, who have already been stretched to the limit, are now being called on to create and nurture genuine connection, psychological safety, and well-being across their organizations-all while adapting to the values of a new generation that won't compromise on diversity, equity, and inclusion. As this book shows, human beings are wired to care, and we can become more empathic with practice. Empathy increases dopamine, reduces stress, boosts self-esteem, heightens the immune system, and enriches our relationships. Empathy also improves business key performance indicators. This means that leveraging empathy on purpose can lead to better health, happier and more productive workplaces, and a more meaningful life. That's why empathy is our superpower. Through inspiring stories; interviews with experts, including business leaders, neuroscientists, activists, social entrepreneurs, and spiritual leaders; a new model rooted in positive psychology and coaching; and self-development exercises at the end of each chapter, Purposeful Empathy offers wisdom and practical advice to foster personal, organizational, and social transformation.